Hubungan Asupan Lemak, Asupan Natrium Dan Status Gizi Dengan Tekanan Darah Sistolik Pada Wanita Pralansia Di Pos Kesehatan Lansia Kelurahan Bojongbata Kecamatan Pemalang Kabupaten Pemalang - Puspita, Nina Arum; , Susi Dyah Puspowati, SP., M.Si; , Rustiningsih, SKM., M.Kes (2016)
Introduction: Center elderly health in Bojongbata village has 44,4% of pre elderly women who had high blood pressure. Factors that caused that problem such as higher fat and sodium intake also lack of activity associated with obesity. Objective: The aim of study was to acses the relationship of fat intake, sodium intake and nutritional status and systolic blood pressure in pre elderly woman in the post of elderly health of Bojongbata, Pemalang. Methods: The research used cross sectional approach. The number of sample was 42 people according to the inclusion criteria. That was covected using consecutive sampling. Retrieval data of fat and sodium intake were done by using semiquantitative FFQ. The category of nutritional status was obtained from the index of body mass. Blood pressure was obtained using a sphygmomanometer. The statistical test used Pearson product moment. Results: The results showed that 42.9% (18 people) of the subjects had the higher of fat intake, 57.1% ( 24 people) of the subjects had the higher of sodium intake, and 40.5% (17 people) of the subjects had the first level of obesity nutritional status category. The highest blood pressure had systolic blood pressure category hypertension as much as 45.2% (19 people). There was a correlation between fat intake and systolic blood pressure (p = 0.048), moreover there was a correlation between sodium intake and systolic blood pressure (p = 0.000), and there was a correlation between nutritional status and systolic blood pressure (p = 0.044). Conclusion: This study concluded that there was a relationship of fat intake, sodium intake, nutritional status with systolic blood pressure.